2020
DOI: 10.1111/apt.15754
|View full text |Cite
|
Sign up to set email alerts
|

A disease‐specific decline of the relative abundance of Bifidobacterium in patients with autoimmune hepatitis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 33 publications
3
68
0
Order By: Relevance
“…Previous research found that a reduced number of fecal anaerobes, represented by the disease-specific decline of Bifidobacterium , occurred in AIH patients ( 7 , 38 ). Our preliminary study found that early intervention of B420 could alleviate liver injury in concanavalin A (Con A) induced hepatitis mice model and decrease the expression of proinflammatory cytokines in the liver tissues ( Supplementary Figures 1A–C ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous research found that a reduced number of fecal anaerobes, represented by the disease-specific decline of Bifidobacterium , occurred in AIH patients ( 7 , 38 ). Our preliminary study found that early intervention of B420 could alleviate liver injury in concanavalin A (Con A) induced hepatitis mice model and decrease the expression of proinflammatory cytokines in the liver tissues ( Supplementary Figures 1A–C ).…”
Section: Resultsmentioning
confidence: 95%
“…In a Chinese cohort, disease-associated dysbiosis in steroid treatment-naïve AIH patients was characterized by reduced biodiversity and decreased abundance of anaerobes ( 6 ). Furthermore, Timur Liwinski et al reported a disease-specific decline of the relative abundance of Bifidobacterium in patients with AIH ( 7 ), which suggested that probiotics might potentially exhibit a beneficial effect in AIH. Bifidobacterium is one of the most important bacterial groups found in the human intestinal tract and its characteristics and mechanism of action have been reported since 1950 ( 8 – 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The microbial communities of human gut were mainly composed of Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria at the phylum level (Dekaboruah et al, 2020). Firmicutes and Proteobacteria were increased in both AIH and PBC, while Bacteroidetes showed no significant difference in AIH and PBC when compared to healthy control (HC) (Lv et al, 2020). Remarkably, PSC was characterized by abundant Bacteroidetes and Proteobacteria, whereas Firmicutes were underrepresented (Sabino et al, 2016;Ruhlemann et al, 2019).…”
Section: The Microbiome In Autoimmune Liver Diseasesmentioning
confidence: 99%
“…Because AIH patients have impaired integrity of intestinal tight junctions, they also have intestinal flora imbalance, characterized by decrease of bifidobacteria, and changes in fecal microbes of specific diseases have been found. AIH patients may have bacterial flora migration, and intestinal barrier dysfunction and bacterial translocation are related to disease severity/increased activity[ 21 ]. Study of the changes in the composition and function of the intestinal microbiome in AIH, using the intestinal microbiota as a non-invasive biomarker, can be used to assess disease activity[ 22 ].…”
Section: Environmental Factorsmentioning
confidence: 99%